Meta-Analysis of Genome-Wide Association Studies Identifies Genetic Risk Factors for Stroke in African Americans. Issue 8 (August 2015) - Carty, Cara L.; Keene, Keith L.; Cheng, Yu-Ching; Meschia, James F.; Chen, Wei-Min; Nalls, Mike; Bis, Joshua C.; Kittner, Steven J.; Rich, Stephen S.; Tajuddin, Salman; Zonderman, Alan B.; Evans, Michele K.; et al.
Abstract : Background and Purpose—: The majority of genome-wide association studies (GWAS) of stroke have focused on European-ancestry populations; however, none has been conducted in African Americans, despite the disproportionately high burden of stroke in this population. The Consortium of Minority Population Genome-Wide Association Studies of Stroke (COMPASS) was established to identify stroke susceptibility loci in minority populations. Methods—: Using METAL, we conducted meta-analyses of GWAS in 14 746 African Americans (1365 ischemic and 1592 total stroke cases) from COMPASS, and tested genetic variants with P <10 −6 for validation in METASTROKE, a consortium of ischemic stroke genetic studies in European-ancestry populations. We also evaluated stroke loci previously identified in European-ancestry populations. Results—: The 15q21.3 locus linked with lipid levels and hypertension was associated with total stroke (rs4471613; P =3.9×10 −8 ) in African Americans. Nominal associations ( P <10 −6 ) for total or ischemic stroke were observed for 18 variants in or near genes implicated in cell cycle/mRNA presplicing ( PTPRG, CDC5L ), platelet function ( HPS4 ), blood–brain barrier permeability ( CLDN17 ), immune response ( ELTD1, WDFY4, and IL1F10-IL1RN ), and histone modification ( HDAC9 ). Two of these loci achieved nominal significance in METASTROKE: 5q35.2 ( P =0.03), and 1p31.1 ( P =0.018). Four of 7 previously reported ischemic stroke loci ( PITX2, HDAC9, CDKN2A/CDKN2B, and ZFHX3 ) were nominally associated ( P <0.05) with stroke in COMPASS. Conclusions—: We identified a novel genetic variant associated with total stroke in African Americans and found that ischemic stroke loci identified in European-ancestry populations may also be relevant for African Americans. Our findings support investigation of diverse populations to identify and characterize genetic risk factors, and the importance of shared genetic risk across populations. Abstract : Supplemental Digital Content is available in the text.